2006
DOI: 10.2165/00019053-200624050-00006
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Weekly Epoetin Alfa versus Biweekly Darbepoetin Alfa for Chemotherapy-Induced Anaemia

Abstract: Most clinical outcome measures suggested greater improvement with epoetin alfa relative to darbepoetin alfa, but most costs for both agents appeared similar. Decision makers must evaluate the differences in costs and efficacy measures that are most relevant from their perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Scenarios of Total Cost Based on DA *This budget impact analysis follows trends found by other previous economic analyses comparing DA and EA, with DA having some cost advantage over EA or being relatively comparable in price [34]…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Scenarios of Total Cost Based on DA *This budget impact analysis follows trends found by other previous economic analyses comparing DA and EA, with DA having some cost advantage over EA or being relatively comparable in price [34]…”
supporting
confidence: 64%
“…One additional older analysis conducted by Reed and colleagues examined costs between 40 000 IU EA QW versus 200 mcg DA Q2W among 358 patients with solid-tumor cancers and CIA over the course of 16-weeks in an open-label, multicenter, randomized trial. 34 In contrast to our cost analysis, the Rubin and colleagues' analysis, and the Song and colleagues' analysis, Reed and colleagues did not assess EA Q3W dosing administration and instead examined off-label Q2W dosing administration. Mean total costs calculations included costs for study medications and their administration, inpatient care, transfusions, unplanned radiation therapy, hematology and laboratory services, chemotherapy and non-chemotherapy drugs and indirect costs in 2004/2005 US dollar values.…”
Section: Resultsmentioning
confidence: 87%
“…In an economic analysis of a randomized controlled trial, the mean total medical care costs for once-weekly EA 40 000 U were $US14 976 and for every other week DA 200 mg were $US14 101 (year 2004-5 values). [12] In this study by Reed et al [12] the cost of medications and their administration was the largest contributor to total medical care costs, and while this study found that these costs were less for patients receiving DA than for those receiving EA, it concluded that this difference was not statistically different. This cost comparison from a randomized controlled trial provides an internally valid comparison of costs; however, these costs may not be seen in general clinical practice outside of a clinical trial setting due to variations in dosing and schedules.…”
Section: Introductionmentioning
confidence: 83%